Remineralization effect of new type of glass ionomer based root canal sealer - Mustafa, Ammar A.; Al-Khateeb, Khalid A. Saeed; Ismail, Ahmad Faris (2011)
Two experimental GIC-based root canal sealers were prepared for the purpose of the study with a main formula of boro tri-fluoro-alumino-silicate (BTFAS) for the test-1 and strontium fluoride SrF2 (99% BDH, Malaysia) for test-2. Ninety specimens of human sound teeth were embedded into an acrylic mould 4x4 cm. A conventional root canal preparation without root canal filling was performed. After sectioning the teeth longitudinally, the internal side of the canal was subjected to a demineralising solution to produce a caries-like lesion. After the end of each demineralizing period, the specimens were rinsed thoroughly with distilled water for 10 minutes and the nail polish was removed. The specimens were examined under transversal micro-radiography to have the (control radiographs). Then a film layer of the experimental sealer test-1 was applied to half of the specimens (n=45) and another film of experimental sealer test-2 was applied to the rest of the specimens (n=45). The test specimens were divided into three time groups to be re-evaluated by transversal micro-radiography (test-radiographs) after 14 days, 28 days, and two months. The specimens were further sectioned and examined under SEM to support the findings of transversal radio-micrograph. The results illustrate a significant difference between the two months test group and the control radiographs but with no significant differences among the other groups. It was obvious that the secondary canals were changed in texture which may be attributed to precipitation of mineral ions by the glass Ionomer sealer. The study needs further investigations to prove the research hypothesis.